Infective endocarditis incidentally discovered by pathological examination. Issue 2 (25th January 2008) - Lepidi, H; Casalta, J-P; Gouriet, F; Collart, F; Habib, G; Raoult, D
Abstract : We present three patients in whom a cardiac valve replacement was needed because of degenerative and supposed non-infectious damage. The excised valves showed histological features of infective endocarditis with detection of micro-organisms. This diagnosis of infective endocarditis was confirmed by other diagnostic methods. Pathological examination of cardiac valves remains the gold standard for the diagnosis of infective endocarditis, and it should be routinely performed even without suspicion of infectious process.